Relationship between Hot Working Climate and Subjective Complaints in Labor in the Loading and Unloading Section at PT. Teluk Bayur Padang Container Terminal IPC - Asih, Wenny Murdina; Herlina, Yeni (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
IPC Container Terminal is one of the subsidiaries of PT. Pelabuhan Indonesia II (Persero) for container terminal services engaged in port and logistics services. If you pay attention to the working environment conditions at PT. The IPC Container Terminal at the loading and unloading section of goods is not equipped with ventilation/air exchange. The purpose of this study was to determine the relationship between a hot working climate and the subjective complaints of workers in the loading and unloading division of PT. Teluk Bayur Padang Container Terminal IPC. The research design is cross-sectional. The research population is stevedoring workers at PT. Teluk Bayur Padang Container Terminal IPC with a total of 46 people. All populations are used as research samples. This research took place from February to August 2022 and the research instrument used a questionnaire. Based on the results of the study, measurement of the temperature of the hot working climate in the loading and unloading section of PT. IPC Teluk Bayur Padang Container Terminal in 2022 obtained an average result of 32.03 0C for all measurement points, this is included in the high category. More than half of the workforce experienced high subjective complaints, namely 73.9%. It is hoped that the management of PT. Teluk Bayur Padang Container Terminal IPC carried out introduction and acclimatization, planting mahogany and matoa trees, adding ventilation for loading and unloading of goods and providing drinking water plus salt, and providing personal protective equipment.